2021
DOI: 10.1111/abac.12215
|View full text |Cite
|
Sign up to set email alerts
|

Does Internal Corporate Governance Complement or Substitute for External Auditing? Evidence from China's Anti‐corruption Campaign

Abstract: Two competing hypotheses have been developed for the relationship between internal corporate governance and external auditing. One proposes a complementary relationship, while the other suggests it is substitutable. This study takes advantage of China's recent anti‐corruption campaign as a quasi‐natural experiment to explore this relationship. Using a difference‐in‐differences approach, we find that, after the campaign, internal corporate governance improved more in SOEs (state‐owned enterprises) than in non‐S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…e Chinese government's anticorruption campaign demonstrates its desire to improve governance quality, which may result in a better institutional environment and benefits for long-term economic development. Research based on China's anticorruption campaign has shown that it does improve internal corporate governance in SOEs at the firm level [46]. However, whether the anticorruption campaign's improved corporate governance has an impact on decision-making in the context of Chinese CBMAs has not yet been fully understood.…”
Section: Further Analysis: Difference-in-difference (Did) Analysis Of...mentioning
confidence: 99%
“…e Chinese government's anticorruption campaign demonstrates its desire to improve governance quality, which may result in a better institutional environment and benefits for long-term economic development. Research based on China's anticorruption campaign has shown that it does improve internal corporate governance in SOEs at the firm level [46]. However, whether the anticorruption campaign's improved corporate governance has an impact on decision-making in the context of Chinese CBMAs has not yet been fully understood.…”
Section: Further Analysis: Difference-in-difference (Did) Analysis Of...mentioning
confidence: 99%